Biological Networks Underlying Abiotic Stress Tolerance in Temperate Crops--A Proteomic Perspective - Kosová, Klára; Vítámvás, Pavel; Urban, Milan Oldřich; Klíma, Miroslav; Roy, Amitava; Prášil, Ilja Tom (International journal of molecular sciences, 2015)
Abiotic stress factors, especially low temperatures, drought, and salinity, represent the major constraints limiting agricultural production in temperate climate. Under the conditions of global climate change, the risk of damaging effects of abiotic stresses on crop production increases. Plant stress response represents an active process aimed at an establishment of novel homeostasis under altered environmental conditions. Proteins play a crucial role in plant stress response since they are directly involved in shaping the final phenotype. In the review, results of proteomic studies focused on stress response of major crops grown in temperate climate including cereals: common wheat (Triticum aestivum), durum wheat (Triticum durum), barley (Hordeum vulgare), maize (Zea mays); leguminous plants: alfalfa (Medicago sativa), soybean (Glycine max), common bean (Phaseolus vulgaris), pea (Pisum sativum); oilseed rape (Brassica napus); potato (Solanum tuberosum); tobacco (Nicotiana tabaccum); tomato (Lycopersicon esculentum); and others, to a wide range of abiotic stresses (cold, drought, salinity, heat, imbalances in mineral nutrition and heavy metals) are summarized. The dynamics of changes in various protein functional groups including signaling and regulatory proteins, transcription factors, proteins involved in protein metabolism, amino acid metabolism, metabolism of several stress-related compounds, proteins with chaperone and protective functions as well as structural proteins (cell wall components, cytoskeleton) are briefly overviewed. Attention is paid to the differences found between differentially tolerant genotypes. In addition, proteomic studies aimed at proteomic investigation of multiple stress factors are discussed. In conclusion, contribution of proteomic studies to understanding the complexity of crop response to abiotic stresses as well as possibilities to identify and utilize protein markers in crop breeding processes are discussed.
Keywords: rostlinné proteiny; fyziologický stres; Proteome; Plant Proteins; Stress, Physiological; Adaptation, Biological; Proteomics; Genotype; proteomika; genotyp; biologické markery; zemědělské plodiny; proteom; Biomarkers; Crops, Agricultural; biologická adaptace